2000
DOI: 10.1007/s002130050040
|View full text |Cite
|
Sign up to set email alerts
|

Local administration of mu or kappa opioid agonists attenuates capsaicin-induced thermal hyperalgesia via peripheral opioid receptors in rats

Abstract: Rationale-By acting on peripheral opioid receptors, opioid agonists can attenuate nociceptive responses induced by a variety of agents.Objectives-This study was conducted to characterize capsaicin-induced thermal hyperalgesia in rats and to evaluate the hypothesis that local administration of either mu or kappa opioid agonists (fentanyl and U50, 488, respectively) can attenuate capsaicin-induced nociception.Methods-Capsaicin was administered s.c. in the tail of rats to evoke a nociceptive response, which was m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 33 publications
0
19
0
Order By: Relevance
“…To ensure an active dose of opioid drug was being administered in the forced swim assay, some groups of rats were subjected to the rat warm water tail withdrawal assay (Ko et al 2000) to measure antinociception with SNC80, morphine and CI977. The warm water tail withdrawal assay was performed one week before the forced swim assay was commenced.…”
Section: Warm Water Tail Withdrawal Assaymentioning
confidence: 99%
“…To ensure an active dose of opioid drug was being administered in the forced swim assay, some groups of rats were subjected to the rat warm water tail withdrawal assay (Ko et al 2000) to measure antinociception with SNC80, morphine and CI977. The warm water tail withdrawal assay was performed one week before the forced swim assay was commenced.…”
Section: Warm Water Tail Withdrawal Assaymentioning
confidence: 99%
“…To this end, capsaicin was injected into the distal portion of the rat's tail, and hyperalgesia was quantified by measuring the tail-withdrawal latency from 45°C water (Ko et al, 2000). A second purpose was to compare the ability of the -opioids morphine, buprenorphine and dezocine to reverse this hyperalgesia in male and female rats.…”
mentioning
confidence: 99%
“…With the [ 35 S]GTPγS binding assay, a classical functional measurement for receptor activation that can be used to determine the potencies and efficacies of opioid ligands at opioid receptors [25] , we found that MB- It have been well demonstrated that κ-agonists produce potent antinociception in different animal pain models [9,[11][12][13] . Our findings were similar to these studies in that we found that MB-1C-OH produced a significant antinociceptive effect in the acetic acid-induced writhing test via κ-but not µ-or δ-opioid receptors.…”
Section: Discussionmentioning
confidence: 99%
“…The precise mechanisms of MB-1C-OH-induced antinociception are of great interest and need to be elucidated in future studies. Many recent studies have shown that κ-opioid agonists produced analgesic effect via peripheral κ-opioid receptor [9][10][11][12][13] without producing undesirable side effects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation